2022
DOI: 10.21203/rs.3.rs-1957883/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic variability predicting breeding potential of upland cotton (Gossypium hirsutum L.) for high temperature tolerance

Abstract: Background High temperature stress at peak flowering stage of cotton is a major hindrance for crop productivity. This study aimed to increase genetic divergence regarding heat tolerance in newly developed cultivars and hybrids. The fifty cotton genotypes and 40F1 were tested under field conditions following the treatments viz., high temperature stress and control at peak flowering stage during August and October under April and June sowing, respectively. Results The means squares revealed significant differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
3
1
0
Order By: Relevance
“…The results showed that genotypes, parents, crosses, parents vs. crosses, lines, testers and line x tester recorded highly significant for all studied traits except for uniformity index of lines. Similar results were reported by Lingaraja et al (2017), Tigga et al, (2017), Al-Hibbiny et al, (2020, , Samak et al, (2022) and Farooq et al, (2023).…”
Section: Analysis Of Variancesupporting
confidence: 90%
See 2 more Smart Citations
“…The results showed that genotypes, parents, crosses, parents vs. crosses, lines, testers and line x tester recorded highly significant for all studied traits except for uniformity index of lines. Similar results were reported by Lingaraja et al (2017), Tigga et al, (2017), Al-Hibbiny et al, (2020, , Samak et al, (2022) and Farooq et al, (2023).…”
Section: Analysis Of Variancesupporting
confidence: 90%
“…High differences between broad and narrow sense heritabilities may be due to the presence of non-fixable components in the inheritance of most traits studied. Similar results were observed by Vadodariya et al, (2017), El-Shazly (2018), Al-Hibbiny (2020), Farooq et al, (2023), Yehia et al, (2023) and Sukrutha et al, (2023).…”
Section: Heritabilitysupporting
confidence: 86%
See 1 more Smart Citation
“…ADN123, ADN413, ADN710, AGC208, Aydın110, BA440, Bir781, Bomba, Bossa159, Candia, Carisma, Carla, Carmen, Ceykot340, Claudia, Çukurova1518, DP332, DP499, Edessa, Efe, Ergüven, ES1, ES2, Esperia, Fantom, Fiona, Furkan, Gloria, GW2345, Harem1, Harem2, İpek607, Kartanesi, Lima, Lodos, MAY404, MAY455, MAY505, Optasia, Özaltın112, Özaltın404, Özbek105, Penta (Golda), PG2018, Sarıgelin, SC2009, SC2079, Sezener76 , SJU86, ST474, ST478, ST498, STV468, Tamcot Spnhix, TMN18, TYA366, Yıldırım63, Zena1010, Zena1018, Zena1040 and ZN243 cotton genotypes (62 pieces) were determined to have in the sensitive region (SZ). In our study, our findings obtained by measuring different values as a result of screening genotypes in terms of vegetative tolerance or sensitivity under control and stress conditions in terms of CMT or %RCI characteristics were similar to the findings of Sajid [33], Azhar [24], Rahman [23], Farooq [34], Zafar [35], Jamil [36]. It was determined that there was a wide variation among the genotypes screened for vegetatively high temperature stress.…”
Section: Leaf High Temperature Stress Index (Lhtsi)supporting
confidence: 87%